Real-time process monitoring and closed-loop control on laser power via a customized laser powder bed fusion platform - Wang, Rongxuan; Standfield, Benjamin; Dou, Chaoran; Law, Andrew C.; Kong, Zhenyu James (Additive manufacturing, 2023)
Additive manufacturing (AM) is one of the most effective ways to fabricate parts with complex geometries using various materials. However, AM also suffers from printing quality issues resulting from the defects such as over-melt, lack of fusion, swelling, etc. One of the root causes of those issues is that the process parameters remain constant during the entire printing process, regardless of the dynamic heat accumulation and various printing feature sizes. For instance, raster is the most common scanning strategy in the laser powder bed fusion (L-PBF) process. The length of the raster line varies depending on the printing feature size. When scanning small features, the raster line is short, resulting in heat accumulations and over-melt. These variabilities may cause severe quality issues and thus suggest adaptive process parameters be applied. Aiming to address this challenge, this study develops a closed-loop control system to regulate the laser power based on melt pool thermal emission to avoid over-melt, balling, and high surface roughness. The control target is determined by correlating the printing quality (dimensional printing error in this study) with the thermal emission through thin-line printing trials using variable power. A high-speed thermal sensor and controller are designed, tuned, and implemented on a newly developed L-PBF testbed. The system successfully maintains a low dimensional error by regulating the laser power at 2 kHz. A significant improvement in printing quality was achieved, as validated by both microscopic imaging and 3D scanning. •Design and implement a customized laser powder bed fusion testbed.•Propose a high-speed and real-time thermal sensor and control system.•Correlate dimensional accuracy and printing temperature to determine the control setpoint.•Controller effectiveness is validated by a high spatial-resolution 3D scanner.